The Pillow Book of Sei Shōnagon - Morris, Ivan (Columbia University Press, 2018)
The Pillow Book of Sei Shonagon is a fascinating, detailed account of Japanese court life in the eleventh century. Written by a lady of the court at the height of Heian culture, this book enthralls with its lively gossip, witty observations, and subtle impressions. Lady Shonagon was an erstwhile rival of Lady Murasaki, whose novel, The Tale of Genji, fictionalized the elite world Lady Shonagon so eloquently relates. Featuring reflections on royal and religious ceremonies, nature, conversation, poetry, and many other subjects, The Pillow Book is an intimate look at the experiences and outlook of the Heian upper class, further enriched by Ivan Morris's extensive notes and critical contextualization.
Keywords: Sei Shōnagon, -- approximately 967- -- Makura no sōshi.; Sei Shōnagon, -- approximately 967- -- Translations -- History and criticism.; Makura no sōshi -- Translations.; Sei Shōnagon, -- approximately 967-; Makura no sōshi (Sei Shōnagon); Japanese literature -- Heian period, 794-1185 -- History and criticism.; Women authors, Japanese -- Heian period, 794-1185.; East and West in literature.; Translating and interpreting -- Cross-cultural studies.; Electronic books.; Littérature japonaise -- 794-1185 (Époque de Heian) -- Histoire et critique.; Écrivaines japonaises -- 794-1185 (Époque de Heian); Orient et Occident dans la littérature.; Livres numériques.; e-books.; LITERARY CRITICISM -- Asian -- Japanese.; HISTORY -- Asia -- Japan.; East and West in literature; Japanese literature -- Heian period; Translating and interpreting; Translations; Women authors, Japanese -- Heian period; 794-1185; Criticism, interpretation, etc.; Cross-cultural studies